2016
DOI: 10.4314/tjpr.v15i4.15
|View full text |Cite
|
Sign up to set email alerts
|

<i>Indigofera tinctoria</i> Linn (Fabaceae) attenuates cognitive and behavioral deficits in scopolamine-induced amnesic mice

Abstract: Purpose: To investigate the cognition-enhancing effects of aqueous extract of Indigofera tinctoria Linn (ITE, Fabaceae)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Indigofera -the plant that gives "indigo" dye belongs to the leguminous family and has about 800 species [1].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indigofera -the plant that gives "indigo" dye belongs to the leguminous family and has about 800 species [1].…”
Section: Methodsmentioning
confidence: 99%
“…When studying the effect of the Indigofera plant on soil salinity in improving the productivity of degraded soils in the soil-climatic conditions of Khorezm region, the indicators of the dynamics of the reduction of salts in the soil were chlorine ion -0.037%; It was observed that SO4 -0.0028%, dry residue decreased to 0.01% and pH decreased to 0.07% [1].…”
Section: Methodsmentioning
confidence: 99%